Socio-demography, nutritional status, age-appropriate immunization coverage and morbidity among under-five children in rural Maharashtra - C. S., Jayalekshmi; Birajdar, Shrikant S.; Gurav, Ravindra B. (International Journal Of Community Medicine And Public Health, 2023)
Background: Morbidities among under-five children in rural areas is a major public health problem. This study was conducted to assess the nutritional status, age-appropriate immunization coverage, personal hygiene and morbidity pattern among under-5 children and their socio-demographic determinates in rural slum dwellings. Methods: A community based cross sectional study was conducted in rural area of Maharashtra using purposive sampling technique. The survey was done by using predesigned and pretested proforma along with recording of socio-demographic factors, anthropometric measurements, immunization status and clinical examination of the study subjects. Results: The study included 86 under-5 children from a rural slum dwelling. 16 (18.60%) subjects were underweighted, 35 (40.70%) were stunted and 14 (16.28%) were wasted. 04 (04.65%) and 02 (02.33%) subjects were MAM and SAM respectively. 35 (40.70%) subjects were morbid. 20 (23.26%) subjects were suffering from louse infestation of which 07 (14.58%) were boys and 13 (34.21%) were girls (p<0.05). 17 (19.77%) subjects were suffering from dental caries. 12 (13.95%) subjects were suffering from skin diseases. 23 (26.74%) subjects were suffering from oral health problems. All subjects’ personal hygiene was poor. 72 (83.72%) subjects were age-appropriate fully immunized. The association between monthly family income and presence of stunting among the subjects is statistically significant (p<0.05). Conclusions: Underweight, stunting, wasting, MAM, SAM, louse infestation, skin diseases, dental caries, oral health problems and poor immunization coverage are found to be major health problems among the under-five children in rural areas. Poor personal hygiene of under-5 children is also a major issue. Capacity building of parents for early health seeking and strengthening of primary health care services is essential to act timely in managing these morbidities.